High risk - Raffill, Stewart; Daly, John; Green, Gerald; Raffill, Joseph; Brown, Robert; Walls, Tom Jr. (La Crosse, Wis. Platinum Disc Corp., 1981)
James Brolin stars as one of four friends sick and tired of working hard and being paid little. They decide to take a trip to Columbia to steal money from a reputed drug lord. According to the plan they'll walk in, get the money, and head back to the states via two airplane pilots they've hired that more resemble Cheech and Chong than they do pilots. Naturally, things don't work out as planned and the chase is not!
Art diretor, Ron Foreman ; Cinematography, Alex Phillips, Jr.
Anthony Quinn, James Brolin, Lindsay Wagner, James Coburn, Bruce Davison.
Not for children.
In English.
Keywords: Adventure films